Reproducible measurable residual disease detection by multiparametric flow cytometry in acute myeloid leukemia - Roehnert, Maximilian A.; Kramer, Michael; Schadt, Jonas; Ensel, Philipp; Thiede, Christian; Krause, Stefan; Buecklein, Veit; Hoffmann, Joerg; Jaramillo, Sonia; Schlenk, Richard F.; Roellig, Christoph; Bornhaeuser, Martin; et al. (Leukemia, 2022)
Measurable residual disease (MRD) detected by multiparametric flow cytometry (MFC) is associated with unfavorable outcome in patients with AML. A simple, broadly applicable eight-color panel was implemented and analyzed utilizing a hierarchical gating strategy with fixed gates to develop a clear-cut LAIP-based DfN approach. In total, 32 subpopulations with aberrant phenotypes with/without expression of markers of immaturity were monitored in 246 AML patients after completion of induction chemotherapy. Reference values were established utilizing 90 leukemia-free controls. Overall, 73% of patients achieved a response by cytomorphology. In responders, the overall survival was shorter for MRDpos patients (HR 3.8, p = 0.006). Overall survival of MRDneg non-responders was comparable to MRDneg responders. The inter-rater-reliability for MRD detection was high with a Krippendorffs alpha of 0.860. The mean time requirement for MRD analyses at follow-up was very short with 04:31 minutes. The proposed one-tube MFC approach for detection of MRD allows a high level of standardization leading to a promising inter-observer-reliability with a fast turnover. MRD defined by this strategy provides relevant prognostic information and establishes aberrancies outside of cell populations with markers of immaturity as an independent risk feature. Our results imply that this strategy may provide the base for multicentric immunophenotypic MRD assessment.
CRIS-Team WoS Importer:2022-07-29